2013
DOI: 10.1371/journal.pone.0061203
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Profiles in the Midgut of Triatoma infestans Infected with Trypanosoma cruzi

Abstract: Chagas disease, or American trypanosomiasis, is a parasitic disease caused by the protozoan Trypanosoma cruzi and is transmitted by insects from the Triatominae subfamily. To identify components involved in the protozoan-vector relationship, we constructed and analyzed cDNA libraries from RNA isolated from the midguts of uninfected and T. cruzi-infected Triatoma infestans, which are major vectors of Chagas disease. We generated approximately 440 high-quality Expressed Sequence Tags (ESTs) from each T. infestan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 50 publications
1
34
0
1
Order By: Relevance
“…APD activity levels increase in the posterior midgut of R. prolixus upon T. cruzi colonization [50]. This finding is also supported by differential APD expression in the midgut of infected/uninfected T. infestans [51]. In all ectoparasite vectors, studies on the interaction of intestinal digestive proteases with symbionts or transmitted pathogens will be necessary to understand how microorganisms establish in this harsh environment, and future work to elucidate this interplay will be essential.…”
Section: Apds Of Ectoparasitic Arthropodsmentioning
confidence: 82%
“…APD activity levels increase in the posterior midgut of R. prolixus upon T. cruzi colonization [50]. This finding is also supported by differential APD expression in the midgut of infected/uninfected T. infestans [51]. In all ectoparasite vectors, studies on the interaction of intestinal digestive proteases with symbionts or transmitted pathogens will be necessary to understand how microorganisms establish in this harsh environment, and future work to elucidate this interplay will be essential.…”
Section: Apds Of Ectoparasitic Arthropodsmentioning
confidence: 82%
“…Interestingly, their observed masses are below the expected ones suggesting the presence of the processed form. Although the function of these enzymes in the AM is not clear, it has been observed that cathepsin D gene expression increases during T. cruzi infection suggesting its potential implication in parasite–host interaction.…”
Section: Protein Classification Associated With Cellular Functionmentioning
confidence: 99%
“…The spot position (below 15 kDa) suggests that the protein has lost its signal peptide and is thus active. The enzyme has been related to trypanosome infection as its expression level increases in the AM upon Triatoma infestans infection . It has as well been related to the digestion of R. prolixus symbiont Rhodococcus rhodnii .…”
Section: Protein Classification Associated With Cellular Functionmentioning
confidence: 99%
“…Reactions were submitted to 36 cycles of 96ºC -10 sec, 50ºC -10 sec and 60ºC -4 min, followed by precipitation with ethanol and sodium acetate buffer. DNA sequencing was carried on an ABI 3130 sequencer (Applied Biosystems) as described by Buarque et al (2013).…”
Section: Cdna Library Construction and Sequencingmentioning
confidence: 99%